ORTHODOXY AS A FACTOR OF UKRAINIAN CIVILIZATIONAL IDENTITY - Shamsutdynova-Lebediuk, Tetyana; Lischuk, Oleksandr (Sworld-Us Conference proceedings, 2025)
The article examines the role of religious identity, particularly Orthodox, in the context of shaping Ukrainian cultural and civilizational self-awareness. Emphasis is placed on the significance of the religious factor as an integrative element influencin